Clonal integration affects growth and sediment properties of the first ramet generation, but not later ramet generations under severe light stress. (28th February 2022) - Ma, Xiaowen; Li, Yang; Yu, Weicheng; Wang, Junnan; Liu, Chunhua
Abstract: Clonal integration benefits clonal plants by buffering environmental stress and increasing resource extraction efficiency. However, the number of connected ramet generations that benefit from clonal integration in a clonal system has received relatively little attention. A pot experiment was conducted to evaluate the extent of physiological integration within the clonal system of Vallisneria natans consisting of a mother ramet and three sequentially connected offspring ramets. Mother ramets were grown in full sunlight, and offspring ramets were heavily shaded with limited light availability. Stolons between mother ramets and offspring ramets were severed or connected, but connection among the three offspring ramets remained. The photosynthetic ability of unshaded mother ramets of V. natans was significantly enhanced, but their biomass accumulation was greatly reduced when connected to shaded offspring ramets. Clonal integration significantly increased biomass accumulation, C and N availabilities, extracellular enzyme activities and microbial biomass of the first ramet generation (adjacent ramet), but not later ramet generations. Our results indicate that support from the mother ramet of V. natans may be limited to the adjacent offspring ramet in a clonal system under severe light stress, implying an effect of ramet generation. Our results contribute to a better understanding of the hierarchy and segmentation of clonal plants. These findings suggest that the extent of clonal integration plays a vital role in ecological interactions of the ramet population. Graphical Abstract: